LEARNING TRAINING IN CONTINUED TRAINING PROGRAMS IN BRAZIL AND PORTUGAL: TEACHER REPRESENTATIONS - Valiengo, Amanda; Lima, Elieuza Aparecida de [UNESP]; Sampaio, Mariana (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2017)
This article has as its theme the representation of teachers on two proposals for continuing education in Brazil and Portugal: the Letter and Life Program and the National Portuguese Teaching Program, in which it deals particularly with the formation of the reader. The discussion is based on a doctoral thesis, whose general objective was the analysis of the representations of teachers on the National Program of Teaching of Portuguese and on the Letter and Life Program. In this exhibition, we present to the analysis representations of the investigated teachers about the impacts of the continued formation in their practices as formators of new readers. The qualitative research was carried out from the narrative of ten teachers. One of the results of the investigation indicates that the teachers indicate changes and increase in the periodicity of reading practices, after the realization of the Programs, which can positively impact the process of training of readers.
Keywords: Basic education; Education of the reader; Continuing education program